2016
DOI: 10.1515/bjmg-2016-0002
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genotoxicity of vincristine, vinblastine and vinorelbine in human cultured lymphocytes: a comparative study

Abstract: Vincristine (VCR), vinblastine (VBL) and vinorelbine (VRL) are anticancer agents from the Vinca alkaloid family that have the potential to induce genotoxic effect. The aim of the present study was to compare the genotoxic effect of VCR, VBL and VRL. Levels of 8-hydroxy-2-deoxy guanosine (8-OHdG) and sister chromatid exchanges (SCEs) were measured in cultured human blood lymphocytes treated with VCR, VBL and VRL at concentrations of 0.01 and 0.1 μg/mL. Results showed that VCR, VBL and VRL significantly increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…Although vincristine has been shown to induce DNA damage, our previous studies in neuroblastoma cells in vitro suggested that the enhanced cytotoxicity of vincristine by CBL0137 is not based on a CBL0137-induced inhibition of DNA damage repair. 14,50 This, however, does not preclude that it could be a mechanism of enhancement in leukemia cells and warrants future investigation. Alternatively, based on studies in glioblastoma and small-cell lung cancer, it can be hypothesized that enhancement between CBL0137 and the tested conventional treatment regimens is brought about by a preferential targeting of cancer stem cells by CBL0137, in complement to the actions of conventional chemotherapeutics that are thought to be poorly active against cancer stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although vincristine has been shown to induce DNA damage, our previous studies in neuroblastoma cells in vitro suggested that the enhanced cytotoxicity of vincristine by CBL0137 is not based on a CBL0137-induced inhibition of DNA damage repair. 14,50 This, however, does not preclude that it could be a mechanism of enhancement in leukemia cells and warrants future investigation. Alternatively, based on studies in glioblastoma and small-cell lung cancer, it can be hypothesized that enhancement between CBL0137 and the tested conventional treatment regimens is brought about by a preferential targeting of cancer stem cells by CBL0137, in complement to the actions of conventional chemotherapeutics that are thought to be poorly active against cancer stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…After that, the slides were irradiated using a 350 mm UV lamp and two 15 W tubes lamps at a distance of 7 cm for 35 min at 40 °C. Finally, the slides were rinsed with distilled water, re-stained for 6–8 min with 5% Giemsa stain and then air dried (Khabour et al, 2014, Mhaidat et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Each of the Catharanthus derivatives, namely vinblastine, vincristine, and vindesine, exhibits varying capacity to inhibit net tubulin polymerization and mediate cytostasis [44]. Intriguingly, despite functioning as MT-targeting agents, vincristine, vinblastine, and vinorelbine can also induce extensive oxidative DNA damage [45].…”
Section: Microtubule-targeting Agents (Vinca Alkaloids and Taxanes)mentioning
confidence: 99%
“…Inhibits microtubule polymerization Induces oxidative DNA damage [43,45] Taxane Docetaxel, Paclitaxel Binds to and stabilizes tubulin polymers [140]…”
Section: Topo I Inhibitor Camptothecinmentioning
confidence: 99%